Paymasters and assurance providers: exploring firms' discretion in selecting non-financial auditors - Prajogo, Daniel (Journal of business ethics, 2021)
Ethical issues in non-financial auditing are increasingly under scrutiny and questions have been raised about the impartiality and independence of audits. Among many other problematic issues, firms have discretion to select their assurance providers and are also required to cover the cost of the audit. Previous literature highlighted several consequences of this competitive and client-driven environment. However, research has mainly focused on firm-level investigation of the consequences—in this paper, we enhance this research by also considering assurance providers. Our approach is grounded in legitimacy and institutional perspectives and we study how organizational motives and selection of assurance providers impact the benefits arising from the audit. In particular, we assume that firms select their assurance providers on the basis of audit strictness (substantial auditing) and market credibility (symbolic auditing) and we study the operational and market benefits that arise from the audit. Based on the data collected from 597 firms, we demonstrate that internal motives drive firms to be more likely to select assurance providers that offer audit strictness, while external motives drive firms to be more likely to select assurance providers that offer market credibility. The findings further show that assurance providers associated with auditing strictness have a stronger effect on operational benefits compared to assurance providers that offer market credibility. We also find that firms’ motives alone are important in driving the benefits achieved. These findings provide a basis for exploring the ethical implications of non-financial auditing.